International handbook of forest therapy - Kotte, Dieter, 1956-; Li, Qing, 1970 February 24-; Shin, Won Sop, 1959-; Michalsen, Andreas (Cambridge Scholars Publisher, 2019)
The first International Handbook of Forest Therapy defines the scientific domain of this innovative, evidence-based and timely public health approach. More than 50 authors from around the world are brought together to offer their expertise and insights about forest therapy from a variety of research perspectives. The theoretical discussion of the effects related to the biophilia hypothesis presented here is complemented by research results compiled across the last three decades in the fields of forest medicine and biochemistry from Asia. The book also highlights the latest developments with re.